Peramalan Permintaan Bag Filter Menggunakan Metode Regresi Linear pada Gudang Suku Cadang PT Semen Padang - Khairi, Aziati Ridha; Salma, Fathayatul (Journal of Digital Ecosystem for Natural Sustainability, 2023)
Demand forecasting is the most important thing for every company in running a business. Demand forecasting is an activity of predicting or estimating what will happen in the future using certain techniques. Research to identify forecasting demand for filter bags so that we can maintain stock of goods and find out the number of products in the future in the face of certain obstacles or conditions to reduce the risks or uncertainties faced. Research methods are constant method, linear trend, and quadratic method. In forecasting Bag Filter demand, three methods are used, namely, the constant method, the linear method and the quadratic method. These three methods have different standard error values. The smallest error level is the constant method. Based on constant data, the number of requests for filter bags for April 2022 – March 2023 is 235 filter bags.